Kepemilikan dan Kepemilikan Manajerial terhadap Nilai Perusahaan dengan Ukuran Perusahaan dan Leverage sebagai Variabel Kontrol (Studi Empiris pada Perusahaan yang Terdaftar dalam Index LQ-45 di BEI Periode 2014-2018) - Farich Novrina Sandy; Wisnu Mawardi; Fuad Mas’ud (Universitas Diponegoro, 2020)
In a few decades, research topic on corporate governance attracts much attention from scholars in Indonesia. Different from most of previous studies, I employ attendance of board of director’s meetings, frequency of board of commisioner’s meetings, audit committee size, audit reputation, ownership concentration and manajerial concentration as the determinants in this research. The purpose of this study is to examine the effect of attendance of board of director’s meetings, attendance of board of commisioner’s meetings, audit committee size, audit reputation, ownership concentration and manajerial concentration on firm performance. Sample of this research covers 30 firms listed on Index LQ-45 in Indonesia Stock Exchange period 2014 until 2018. The analysis method used is multiple regression with 150 observations data panel. Firm performance is measured with Tobin’s Q and controlling for firm size and leverage. The results show that attendance of board of director’s meetings, attendance of board of commisioner’s meetings, audit committee size, and manajerial concentration has negative and not significant effect on firm performance. However, the result show that audit reputation and ownership concentration has positive and significant effect on firm performance.